Ambulance-delivered transdermal glyceryl trinitrate versus sham for ultra-acute stroke: Rationale, design and protocol for the Rapid Intervention with Glyceryl trinitrate in Hypertensive stroke Trial-2 (RIGHT-2) trial (ISRCTN26986053). Issue 2 (February 2019) - Appleton, Jason P; Scutt, Polly; Dixon, Mark; Howard, Harriet; Haywood, Lee; Havard, Diane; Hepburn, Trish; England, Tim; Sprigg, Nikola; Woodhouse, Lisa J; Wardlaw, Joanna M; Montgomery, Alan A; et al.
Rationale: Vascular nitric oxide levels are low in acute stroke and donors such as glyceryl trinitrate have shown promise when administered very early after stroke. Potential mechanisms of action include augmentation of cerebral reperfusion, thrombolysis and thrombectomy, lowering blood pressure, and cytoprotection. Aim: To test the safety and efficacy of four days of transdermal glyceryl trinitrate (5 mg/day) versus sham in patients with ultra-acute presumed stroke who are recruited by paramedics prior to hospital presentation. Sample size estimates: The sample size of 850 patients will allow a shift in the modified Rankin Scale with odds ratio 0.70 (glyceryl trinitrate versus sham, ordinal logistic regression) to be detected with 90% power at 5% significance (two-sided). Design: The Rapid Intervention with Glyceryl trinitrate in Hypertensive stroke Trial-2 (RIGHT-2) is a multicentre UK prospective randomized sham-controlled outcome-blinded parallel-group trial in 850 patients with ultra-acute (≤4 h of onset) FAST-positive presumed stroke and systolic blood pressure ≥120 mmHg who present to the ambulance service following a 999 emergency call. Data collection is performed via a secure internet site with real-time data validation. Study outcomes: The primary outcome is the modified Rankin Scale measured centrally by telephone at 90 days and masked to treatment. Secondary outcomes include: blood pressure, impairment, recurrence, dysphagia, neuroimaging markers of the acute lesion including vessel patency, discharge disposition, length of stay, death, cognition, quality of life, and mood. Neuroimaging and serious adverse events are adjudicated blinded to treatment. Discussion: RIGHT-2 has recruited more than 500 participants from seven UK ambulance services. Status: Trial is ongoing. Funding: British Heart Foundation. Registration: ISRCTN26986053.